PENGARUH WORK FAMILY CONFLICT DAN AMBIGUITAS PERAN TERHADAP INTENTION TO QUIT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi pada HOTEL GRAND EDGE SEMARANG) - Munda, Agres Oktavia; Yuniawan, Ahyar (Diponegoro Journal of Management, 2018)
The objectives of this research are to  define and comprehensively analyze the influence  of  work  family  conflict  and  role  ambiguity  towards  intention  to  quit  by conducting  work  stress  as  the  intervening  variable.  This  research  was  conducted  by passing the questionaires to 50 staffs in Grand Edge Hotel, Semarang.It applied multiple regression as method   analysing the data. In testng the data, validity test, reliability test, classical assumption test, and determinant coefficient test, F test, T test, and Test of Sobel were conducted in order to check the mediation effectAs the result, it showed that work family conflict was positively and significanly influenced  work  stress  and  intention  to  quite,  role  ambiguity  was  positively  and significanly influenced work stress and intention to quite. Work stress   was to mediate relation between work family conflict and role ambiguity towards intention to quit.